Autoimmune Diseases and Their Manifestations on Oral Cavity: Diagnosis and Clinical Management - Matteo Saccucci; Gabriele Di Carlo; Maurizio Bossù; Francesca Giovarruscio; Alessandro Salucci; Antonella Polimeni (Journal of Immunology Research)
Oral signs are frequently the first manifestation of autoimmune diseases. For this reason, dentists play an important role in the detection of emerging autoimmune pathologies. Indeed, an early diagnosis can play a decisive role in improving the quality of treatment strategies as well as quality of life. This can be obtained thanks to specific knowledge of oral manifestations of autoimmune diseases. This review is aimed at describing oral presentations, diagnosis, and treatment strategies for systemic lupus erythematosus, Sjögren syndrome, pemphigus vulgaris, mucous membrane pemphigoid, and Behcet disease.